AUDIT REPORT LAG IN MALAYSIA - Apadore, Kogilavani; Tazilah, Mohd Danial Afiq Khamar; Punchanathan, Uma Eswari; Letchumanan, Thanaletchumi (International Journal of Accounting, Finance and Business, 2024)
The nature of the Corporate Governance mechanism in a company may influence the timeliness of the audited financial statement. This study examines the trend of Audit Report Lag (ARL) within Malaysia Public Listed Companies. This study examines data collected between 2011 and 2015 during the IFRS Convergence period, as opposed to data from 2012 in earlier work. This research used balance panel data with 1710 observations for a sample of 342 public listed companies from Bursa Malaysia website. Policymakers, regulators, and academics can all benefit from this study's insightful recommendations on how to ensure that the code of corporate governance is appropriately managed in compliance with Bursa Malaysia's criteria.